2008
DOI: 10.1155/2008/546808
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Temporal, and Interchannel Image Data Fusion for Long‐Distance Terrestrial Observation Systems

Abstract: This paper presents methods for intrachannel and interchannel fusion of thermal and visual sensors used in long-distance terrestrial observation systems. Intrachannel spatial and temporal fusion mechanisms used for image stabilization, super-resolution, denoising, and deblurring are supplemented by interchannel data fusion of visual-and thermal-range channels for generating fused videos intended for visual analysis by a human operator. Tests on synthetic, as well as on real-life, video sequences have confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…This behavior is common when a shooting occurs. We then apply spatial aggregation to the resulting temporal aggregation by considering neighboring cells given by equation (6), which counts the number of neighboring cells that exceed a specific threshold TR. The resulting grid is spatially and temporally aggregated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is common when a shooting occurs. We then apply spatial aggregation to the resulting temporal aggregation by considering neighboring cells given by equation (6), which counts the number of neighboring cells that exceed a specific threshold TR. The resulting grid is spatially and temporally aggregated.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggest the utilization of both audio and video input for event detection and indexing [1]. Other work extends these ideas to include features extracted from the video itself, such as text [2] while some studies suggest the indexing and integration of multiple video streams: these can be sourced from the same modality camera, (e.g., visible light cameras) [3], [4] or from cameras of different modalities (e.g., infrared and visible light) [5], [6]. A comprehensive review of these methods in the context of surveillance can be found in [7]: importantly all these studies utilize data that are extracted solely from video sources, i.e., none of these studies explicitly address the task of combining sources of different modalities for event detection.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic image registration is proposed by J Kybic et al that incorporates geometric mapping that is locally affine and also globally smooths [11]. Elastic image registration technique can also be used in medical imaging is proposed by S. Periaswamy et al [12]. The CLEAR algorithm proposed by N Anantrasirichai et al [1] [13], stabilizes the video by aligning (by translation) the centers of corresponding regions of interest (ROI).…”
Section: Related Workmentioning
confidence: 99%